EFEKTIVITAS WORDWALL SEBAGAI MEDIA GAME-BASED LEARNING DALAM PENINGKATAN PENGUASAAN KOSAKATA DI SDN PASIRHALANG 1 KABUPATEN SUKABUMI - Intan Dwi Persada; Aris Setiawan Muhammadi; Ria Saparianingsih (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to evaluate the effectiveness of Wordwall as a game-based learning medium in improving elementary school students’ English vocabulary mastery. The main problem addressed in this research is the low student engagement and vocabulary proficiency in traditional learning settings. The research was conducted at SDN Pasirhalang 1, Sukabumi Regency, using a pre-experimental design with a quantitative approach through a one-group pretest-posttest model. The instrument used was a multiple-choice vocabulary test consisting of 20 items covering Parts of Speech (Adjective, Noun, Verb, Adverb, Preposition, Possessive Pronoun, and Possessive Adjective), designed across Bloom’s cognitive domains from C1 to C6. The findings indicated an increase in the mean score from 62.4 (pretest) to 77.2 (posttest). The N-Gain analysis revealed an average gain of 0.4019, classified as moderate effectiveness. Furthermore, the Paired Sample t-Test showed a significance value of 0.000 (p < 0.05), indicating a statistically significant difference in learning outcomes before and after the implementation of Wordwall. These results suggest that Wordwall is an effective and engaging digital tool for enhancing students’ vocabulary mastery, making it a viable alternative for vocabulary instruction at the elementary level.